Identification of Preventable Risk Factors for Developmental Delay in Children: A Pilot Study - Tejanjani Vathada; Lokesh Lingappa (Korean Child Neurology Society, 2023)
Purpose Developmental delay (DD) is reported to be frequent in developing countries, such as India. Hence, this study was carried out to evaluate preventable risk factors that can predispose children to DD, through observations of pediatric neurology outpatients. Methods This was a prospective, observational, and descriptive cross-sectional single-center hospital-based study for a period of 30 days, split into two separate time periods due to the impact of the coronavirus disease 2019 pandemic. Children who newly presented to the pediatric neurology outpatient department were considered. There were a total of 151 boys and girls, from 6 months to 14 years of age. Detailed demographic information on prenatal, natal and postnatal risk factors relevant to the neurological diagnosis was collected. Antenatal education for mothers about breastfeeding and newborn care, place of delivery, the availability of round-the-clock pediatric care during the delivery, gestational age, maternal fever, encephalitis, seizures, meningitis, blood pressure, gestational diabetes mellitus, infections, history of consanguinity, and genetic disorders were all considered. The data were analyzed with odds ratios and multivariable logistic regression. Results Forty-three of the 151 enrolled children had DD. Significant associations were found between consanguinity and DD (adjusted odds ratio [AOR], 6.50; 95% confidence interval [CI], 1.96 to 21.51; P<0.002) and between prematurity and DD (AOR, 2.34; 95% CI, 1.07 to 5.13; P<0.033). Conclusion This study shows that consanguineous marriages and prematurity predisposed children to DD when prenatal, natal, and postnatal risk factors were comprehensively considered.